Assessment the concentration of some heavy metals of selected soils from Shattrah city. - احمد كاظم, ابتهاج; طالب جواد, سناء (University of Thi-Qar Journal of Science, 2016)
The aim of this study to measure the concentrations of five heavy elements in the soil of Shattrah city. We try to detect the extent of contamination levels of heavy metal and make comparison between these level and international standard determinants. We were selected (7) different stations in the city including (old crowded residential, industrial, modern crowded residential, Industrial, area exposers  bombed in 2003, and areas closed  to the busy streets to vehicles) samples were collected during the month of June and July of 2016 -2015. Using Atomic Absorption Spectrophotometer device (Flam Atomic absorption). Values were arranged  ​​[(171.6857, (12.27), (66.4142), (21.5), (20.928) ppm] respectively, the present results indicate that there was high ratio of lead, cadmium and zinc in all study areas and another evidence of soil contamination.